As câmaras municipais em juízo - Dantas, Rodrigo Emanuel de Araújo (2024)
The Municipal councils are the political institution that best represents the link between citizens and state power. Their historical importance dates back to the first two centuries of Brazil's colonial period. The challenges faced by Portugal in the process of settling the colonial territory, the high costs involved due to the geographical distance and the failure to meet its mercantilist objectives led to the neglect of the metropolis and the consequent social, economic and political gaps, which determined the primacy of local power. It should be noted that the politicaladministrative structure of the colonial chambers encompassed functions similar to administrative, legislative and jurisdictional activities. Despite having the status of an independent and representative body of the Municipal Legislative Power in the 1988 Federal Constitution, Municipal Councils still suffer from the legal consequences of their absolute depersonalization, the dogma of which, established by the Theory of the organ, has been incorporated into legal systems. In this context, we investigate the role of municipal councils in the necessary defense of their own prerogatives before the Judiciary, whose notion of judicial personality is an essential jurisprudential parameter for the role of constitutional bodies as parties in procedural legal relations. The approach also involves the analysis of doctrinal and jurisprudential aspects, with emphasis on the fundamental contribution of Justice Victor Nunes Leal in defending the rights of Municipal Councils, from the publication of an article in 1949 analyzing a precedent from the Court of Justice of Rio Grande do Sul, which faced the issue of the active legitimacy of Municipal Councils in court. The case law of the Municipal Councils only recognizes their legal personality, and consequent legitimacy to act as an active or passive procedural party, when exercising the defense of their autonomy, functioning or independence, that is, based on a subjective-objective criterion, based on the requirements of the demand. The jurisprudential formula disregards the innate condition of Municipal Councils as subjects of law, endowed with material and formal (procedural) legal capacities, given their various constitutional, legal and regimental competences. The contemporary approach to the role of municipal councils in court requires an analysis of aspects of the General Theory of the State, Constitutional, Administrative, Civil and Civil Procedural Law, including the main dogmas of the Theory of the organ and the Organizational Law of the State. It is necessary to uncover the main obstacles that impede the right of Municipal Councils and other primary bodies of the Brazilian political-administrative organization to have free access to the State's judicial protection, in order to guarantee them the constitutional guarantee of Inafastability of Jurisdiction (art. 5, XXXV of the Federal Constitution)